(3GdeSdc GdLdi aj Mce TWM Gdhdis - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjf,J (B1101 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dg GdehLhOGJ CeG HYO abO hQO SDGd ef HYV s
(3BNQgG (B:s
(3CfGd HgG TQa cQGeJc ai GdOfjG hGdCNQI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG Jedcs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs